Forma canónica y cambios en la forma canónica de la lengua vasca: hacia los orígenes del bisilabismo (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Sketch of the monosyllabic-root theory and its previous results (§2). Implications of the canonical form’s (CF) analysis for the study of typological change and formal etimology (§§3-4). §5 Survey on the CF change of other languages (chinese, tani, munda). Phonic evidences and traces of CF’s change in Basque language’s prehistory (§6). Some implications of the CF change on the verbal roots’ polimorphism (§ 7). Consequences the use of the changing CF has for reconstruction and obtaining of new etymologies (§8). On to the big amount of loan words among B. bysillabic roots, as well as the role those loan words played in the spread of such bysillabic root-type in the language (§9): Late (Middle Ages) cronology of historical bysillabism. §10 Some conclusions.
Keywords: Canonical form; Typological change; Verbal polimorphism; New etymologies; Chronology; Bisyllabism